Effect of different Dosage Infection Ascaridia galli and Piperazine Treatment on Total Worm and Layersâ Body Weight - Zalizar, L; Satrija, F (ANIMAL PRODUCTION, 2009)
The aim of this research was to study effect of different dosage Infection Ascaridia galli (A. galli) and anthelmintic piperazineÂ  treatment to total worm and layersâ body weight. The research was based on Randomized Completely Design with Factorial (3x2) pattern. The first factor was A. galli infected dosage (0, 200x 4 and 2000x 4 infective eggs) and the second was anthelmintic treatments (without and with piperazine treatment). The result showed that until 6 weeks after infection, only larvae were found in chicks, the adult and egg worms were not found.Â  The infection dosages and piperazine treatment influenced the larvae total. Larvae total in light and heavy dose infection that had piperazine treatment lower than group without piperazine. The infection dosages and piperazine treatment influenced body weight two and four weeks after the anthelmintic treatment. Body weight in group with heavy dose infection after two and four weeks had piperazine treatment were higher than group that had heavy dose infection but without Â the anthelmintic medication. Body weight in group with light and heavy dose infection after four weeks had piperazine treatment were not difference with group without infection. The piperazine effication to larvae only reached 69% (ineffective) in light dose and 85% (moderate effective) in high dose infection. (Animal Production 11(3): 176-182 (2009)Â Key Words: Infection dose, Ascaridia galli, piperazine, warm, Â layersâ body weight